2015
DOI: 10.1007/s40519-015-0188-x
|View full text |Cite
|
Sign up to set email alerts
|

Explaining rigid dieting in normal-weight women: the key role of body image inflexibility

Abstract: Restrictive dieting is an increasing behavior presented by women in modern societies, independently of their weight. There are several known factors that motivate diet, namely a sense of dissatisfaction with one's body and unfavorable social comparisons based on physical appearance. However, dieting seems to have a paradoxical effect and has been considered a risk factor for weight gain and obesity in women and for maladaptive eating. Nevertheless, the study of the emotional regulation processes that explain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 34 publications
3
14
0
3
Order By: Relevance
“…The observed effects also extend previous cross-sectional (e.g., Ferreira et al, 2011;Ferreira et al, 2015;Sandoz et al, 2013;Timko et al, 2014;Wendell et al, 2012) research citing body image flexibility as a useful process in possibly mitigating risk of disordered eating in the presence of body dissatisfaction. In line with this emerging evidence in the domain of eating behavior, body image flexibility may also be instrumental in promoting body appreciation when confronting challenges to body image.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The observed effects also extend previous cross-sectional (e.g., Ferreira et al, 2011;Ferreira et al, 2015;Sandoz et al, 2013;Timko et al, 2014;Wendell et al, 2012) research citing body image flexibility as a useful process in possibly mitigating risk of disordered eating in the presence of body dissatisfaction. In line with this emerging evidence in the domain of eating behavior, body image flexibility may also be instrumental in promoting body appreciation when confronting challenges to body image.…”
Section: Discussionsupporting
confidence: 84%
“…Importantly, these effects were retained when global levels of psychological flexibility and a conceptually similar measure of body image avoidance were included in separate regression models (Timko et al, 2014). Finally, path analytic findings from another recent investigation indicated that this approach to relating to one's negative body image-related internal experiences fully mediated the association between the tendency to compare one's physical appearance to peers and the frequency of engaging in an inflexible eating style (Ferreira, Trindade, & Martinho, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…In fact, research conducted with young women from the community demonstrated that psychological inflexibility focused on eating, as measured by the IEQ, was highly linked with other psychological processes that have been demonstrated as central for psychological adjustment and disordered eating. Ferreira, Trindade and Martinho (2015) demonstrated that body image and weight dissatisfaction and unfavorable social comparisons significantly predicted women's levels of psychological inflexibility focused on eating, mediated by the mechanism of body image inflexibility. Duarte, Ferreira, Trindade, and Pinto-Gouveia (2015), in a sample of adolescent girls, found that psychological inflexibility focused on eating was a significant predictor of eating psychopathology.…”
Section: Developed the Cognitive Fusionmentioning
confidence: 95%
“…Body dissatisfaction has been identified as one of the key risk and maintenance factors for eating disorders [1], and also contributes to dysfunctional eating behaviors such as binge eating [2] and rigid dieting [3]. Research based on cognitive theories of eating disorders [4,5] has emphasized the important roles that increased attention to and better memory for body-related information play in the development and maintenance of such body image issues [6], but the exact nature of the relationship between these biases and their impact on women's body image concerns is not well understood.…”
Section: Introductionmentioning
confidence: 99%